Are incisional biopsies reliable for selecting definitive treatment of ameloblastomas? A 15-year interdisciplinary retrospective study. - Renapurkar, Shravan Kumar; Broccoli, Peter; Carrico, Caroline; Glass, Sarah (Oral Surgery, Oral Medicine, Oral Pathology & Oral Radiology, 2022)
Objectives: Sampling error in incisional biopsy can lead to under/overtreatment. The aim of this study is to determine the incidence of sampling error/discordance between incisional biopsy and final diagnosis and consequences for treatment outcomes.Study Design: This study is a retrospective cohort study of patients treated for ameloblastoma at an academic medical center from 2005 to 2020. Patients with minimum of 1 year of follow-up after definitive treatment and complete documentation were included. Clinical variables included radiographic findings, incisional biopsy, and final histopathology. Outcome variables were discordance between incisional biopsy and final pathology as well as recurrence rates. Results are primarily descriptive. Fisher's exact test was used to test for differences in recurrence rates.Results: Twenty-three patients (14 male/9 female) met the inclusion criteria. Overall, discordance was found in 2 cases (8.6%) and sampling error in 3 (13.04%). One of the 3 cases showing sampling error had recurrence and required secondary resection. Six patients (26.1%) had recurrent lesions, and all patients underwent enucleation and curettage with or without peripheral ostectomy.Conclusions: Incisional biopsies by themselves are not always consistent with a final diagnosis. Possibility of sampling error should be included in informed consent. Consultation with an oral pathologist is essential at initial and final histopathologic evaluation.